ChatGPTeachers: Technoethical Attunements of Teaching Practice in AI-Mediated Learning Networks - Groten, Sean; Adams, Cathy; Kowalchuk, Jillian; Shinkaruk, Cheryl; Cunningham, Nicole; Woodruff, Rebecca (Proceedings of the International Conference on Networked Learning, 2026)
The emergence of AI, particularly Generative AI (GenAI), has introduced powerful new actors into learning networks, creating an urgent need for research on how these technologies may be mediating connections between teachers, learners, and other digital technologies and institutional infrastructures. While GenAI extends connectivity across these networks, it also regenerates and reconfigures the conditions of teaching, learning, and professional practices. As a result, questions of professional ethics, teacher identity and agency are becoming central to understanding how teachers’ work is adapting and changing in the context of AI-mediated learning environments. This paper reports on a six-month study in which 20 K-12 teachers in a Canadian urban school division were provided access to ChatGPT Teams. Teachers participated in phenomenologically oriented interviews at the beginning and end of this period. From these accounts, Lived Experience Descriptions (LEDs) were developed to capture moments of tension, hesitation, curiosity and ethical reflection. Through these teacher-ChatGPT anecdotes, we examine how GenAI provokes technoethical tensions in teachers’ everyday work and learning lives, and, in the process, reshapes their planning, communication, and professional identity. Our analysis reveals that teachers encountered manifold technoethical dilemmas when interacting with ChatGPT. Their concerns extended beyond the appropriate use of the LLM to existential questions about their integrity and identity as teachers when using ChatGPT. Teachers experienced ambivalence when using ChatGPT to assist with professional communication or when imagining what it would be like to incorporate it into their pedagogy. Such anecdotes reveal the importance of professional learning that supports ethical discernment in networked learning contexts. Here, we suggest that the Technoethical Framework for Teachers (TEFT) can strengthen teachers’ ethical attunement and agency as they engage with GenAI in their practice. The paper contributes to networked learning scholarship by situating teachers’ encounters with GenAI within relational and ethical ecologies rather than adoption or policy frameworks. It offers implications for NL researchers, teachers reflecting on the ethical implications of their Technological-Pedagogical-Content Knowledge (TPACK) in light of GenAI, and school leaders developing professional learning and policy around the critically informed and responsible use of Large Language Models (LLMs) in schools. Prior studies have described how teachers engage with GenAI; this paper shows how those engagements are ethically charged and ontologically mediated. By framing teachers’ co-constitutive relationships with ChatGPT as technoethical relations of attunement, we offer both a theoretical vocabulary and an empirical method for studying GenAI in education through lived experience and a new conceptual lens.